KEPENTINGAN RUSIA DALAM MENGINTERVENSI KONFLIK PERBATASAN ABKHAZIA DAN OSSETIA SELATAN DI WILAYAH GEORGIA - ", Fakhrunnas; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research describes about the intervention that Russia was made in a border conflict between Abkhazia and South Ossetia against Georgia in Georgia’s territory. The intervention that Russia made finally involved conflict between Russia and Georgia.The research method applies qualitative descriptive method, realism perspective and National Security theory. The author collected data from books, encyclopedia, journal, mass media and website to analyze the form of intervention Russia in a border conflict between Abkhazia and South Ossetia against Georgia, the impact of Russia’s intervene and to analyze Russia’s interest to involve in that conflict. The conclusion of this research is Russia’s interest to getting involved and intervene the conflict is because Rusia wants to reunite former member states of Soviet Union and create a new Communist-Socialist power under its influence and hegemony in Caucasus Region to stem the influence of the United States and NATO. Key words: Russia, Borders Conflict, Influence, Hegemony, NATO, USA, Abkhazia, South Ossetia, Georgia, Intervention,Civil War.